2021
DOI: 10.3390/ma14040882
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mechanical and Thermal Properties of Hemp-Lime Mortar

Abstract: The use of renewable and natural materials characterized by the low environmental impact is nowadays a key issue for the sustainable development of the construction industry. For this reason, the interest for natural fibers, to be used as reinforcement in composites as an alternative to other fibers, is continuously growing. In this paper, the use of hemp for reinforcing lime mortar used as plaster is considered with a multidisciplinary approach, taking into consideration the structural and thermal performance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…A similarly high water vapor transmission rate was reported, e.g., by Silva et al [68], who analyzed blended lime-hydraulic lime mortars. High water vapor permeability of lime mortars was acknowledged also by Parcesepe et al [69]. The cement-lime mortars yielded higher resistance to water vapor transport, which limits their use on masonry suffering from excessive moisture content.…”
Section: Materials ρ B (Kg•mmentioning
confidence: 89%
“…A similarly high water vapor transmission rate was reported, e.g., by Silva et al [68], who analyzed blended lime-hydraulic lime mortars. High water vapor permeability of lime mortars was acknowledged also by Parcesepe et al [69]. The cement-lime mortars yielded higher resistance to water vapor transport, which limits their use on masonry suffering from excessive moisture content.…”
Section: Materials ρ B (Kg•mmentioning
confidence: 89%
“…Previous studies have shown the thermo-mechanical performance of hemp concrete [20][21][22][23][24][25][26] with the limitations of being a non-structural material [27][28][29][30], but at the same time, it excels when it comes to heat transfer and the thermo-regulating capacity of ambient humidity, which makes it recognised as a very good thermal insulation material with a decisive role in increasing the hygro-thermal performance of sustainable constructions [31][32][33]. The fact that it is obtained from natural sources as a by-product of agricultural activities qualifies it in the race for the best products with potential in the circular economy [34] while contributing to the reduction of carbon emissions [35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…All sorts of organic materials available in given geographic regions are utilized as a main layer of a wall or they are added to plaster mortars, where a small amount of the additive introduced in the form of organic fibers may significantly improve the thermal insulation and strength parameters [24]. Another example for improvement of the heat transfer coefficient and thermal inertia of lime mortars is application of the additive in the form of iron (III) oxide [25].…”
Section: Introductionmentioning
confidence: 99%